Study of the Influence Hormone LHRH-a and 17a-MT of Hemocytology on Orange Spot Grouper Broodstock, Epinephelus coioides - F. Johnny; A. Priyono; D. Roza (Jurnal Akuakultur Indonesia)
An experiment to study the influence of the chronic hormone LHRH-a and 17a-MT on haematology orange spot grouper, Epinephelus coioides broodstock was conducted at Gondol Research Institute for Mariculture, Bali.  Fish weights were ranged 4.7-10.4 kg (female) and 10.4-17.8 kg (male).  The females broodstock was treated by hormone 17a-MT with dosage 50 mg/kg body weight, and males was by hormone LHRH-a with dosage 50 and 100 mg/kg body weight.  Fish were kept on two concrete tank contained 100 m3 sea water and 2 meters depth and density 15 fishes/tank,  male ratio and female was 1 : 2.  Hormone treatment was peformed every two months until six months culture.  Blood were collected before treatment by hormone and every two months.  Hemocytology parameters measured were hematocrit, hemoglobin, total erythrocyte, and total leucocyte.  Result of the average indicator of hemacytology to influence on haemological parameters.